1980
DOI: 10.1161/01.hyp.2.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular reactivity in the young spontaneously hypertensive rat.

Abstract: SUMMARYThe renal resistance vessels of the mature spontaneously hypertensive rat (SHR) exhibit increased reactivity to vasoconstrictor agonists. This could be a cause or consequence of hypertension. We have compared vascular reactivity in isolated perfused kidneys from 46-day-old SHR and from normotensive control rats. The amplitude of responses in kidneys from the SHR to angiotensin II, barium chloride, or norepinephrine was not different from the control. Therefore, increased reactivity of the renal vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 22 publications
3
26
2
Order By: Relevance
“…This is in contrast to findings of other investigators, who have obtained greater enhancement of the S-I release of [3H]-noradrenaline by angiotensin II in isolated preparations from SH rats than in those from WKY rats, such as perfused mesenteric vasculature (Eikenburg et al, 1981) and perfused kidneys (Collis et al, 1980 (Gironacci et al, 1994) and guinea-pig isolated atria (Brasch et al, 1993) was blocked by losartan and unaltered by PD 123319. In the rabbit iris ciliary body the enhancement of S-I release of [3H]-noradrenaline by angiotensin II was also blocked by losartan and unaffected by PD 123177 (Ohio & Jumblatt, 1993).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This is in contrast to findings of other investigators, who have obtained greater enhancement of the S-I release of [3H]-noradrenaline by angiotensin II in isolated preparations from SH rats than in those from WKY rats, such as perfused mesenteric vasculature (Eikenburg et al, 1981) and perfused kidneys (Collis et al, 1980 (Gironacci et al, 1994) and guinea-pig isolated atria (Brasch et al, 1993) was blocked by losartan and unaltered by PD 123319. In the rabbit iris ciliary body the enhancement of S-I release of [3H]-noradrenaline by angiotensin II was also blocked by losartan and unaffected by PD 123177 (Ohio & Jumblatt, 1993).…”
Section: Discussioncontrasting
confidence: 97%
“…In some experimental models of hypertension, enhanced facilitation by angiotensin II of transmitter noradrenaline release at sympathetic neuroeffector sites, compared with that in normotensive animals, has been demonstrated (Eikenburg et al, 1981;Westfall et al, 1984). In addition to enhanced facilitation of transmitter release by angiotensin II, enhanced smooth muscle responsiveness to exogenous angiotensin II and other vasoconstrictor stimuli have been obtained in spontaneously hypertensive (SH) rats (Lais & Brody, 1978;Collis et al, 1980). In SH rats, the receptors involved in the prejunctional facilitatory effects of angiotensin II at noradrenaline receptor sites in the heart and some blood vessels have been shown to be blocked by AT1 but not AT2 receptor antagonists (Nagase et al, 1994;Foucart et al, 1994 (Weber, 1992) and in spontaneously hypertensive dogs (Bovee et al, 1991) and SH rats (Wong et al, 1990b).…”
Section: Introductionmentioning
confidence: 99%
“…The results of our present study are in agreement with those of Masuyama et al 20 and in line with those reported by Collis et al, 15 who found more endogenous norepinephrine release on electrical stimulation from the kidney of young SHR (46 days old) than that of normotensive control rats. By use of tissue in vitro labeled with [ 3 H]norepinephrine, Vanhoutte et al 16 -18 also found significantly more tritium overflow from the kidney of young SHR but not in the kidney of adult rats (4-6 months of age) when compared with the normotensive controls whereas Zsoter et al 19 observed more tritium over- 'Significant difference between 7-week-old WKY and SHR by one-way analysis of variance.…”
Section: Discussionsupporting
confidence: 94%
“…Release by K + of endogenous norepinephrine from the coccygeal artery of SHR at all ages was also significantly greater than in WKY rats. 13 However, both Collis and colleagues 14 ' 15 and Vanhoutte and coworkers 16 -18 found an age-related effect with nerve stimulation. More endogenous norepinephrine was released from the kidney of young SHR (46-day-old) 15 but not in the kidney of adult animals (4-6 months) when compared with the normotensive controls.…”
Section: Week-old) Shr As An Indicationmentioning
confidence: 99%
See 1 more Smart Citation